Membangun Ketahanan Keluarga yang Rukun, Harmonis dan Romantis - Ahmad Zuhri Rangkuti (Medan Resource Center, 2021)
This study aims to find out how the residents of Dusun I, Tanjung Keliling Village, Salapian District, Langkat Regency, in building family resilience to face life that is now relatively more difficult. The author uses a qualitative-descriptive method and uses three techniques, namely observation, interviews and literature review and documentation. The results of the study found that education, especially religion, has an important role in building family resilience that is harmonious, harmonious and romantic. Among them are by fostering an attitude of humility, mutual respect, active communication between husband and wife and between parents and children as has been done for years of marriage by the residents of Dusun I. Researchers found a relationship between family attitudes and the practice of religious teachings so that good relations were built as evidenced by the mutual understanding between husband and wife when facing problems, the attitude of accepting children towards deliberation decisions between their parents and or between parents and children. affect the family's economic problems during the pandemic. The results of the study are (1) Optimizing family resilience for every citizen. (2) The concept of every family is needed in dealing with household problems. (3) The economic aspect is a factor that affects family resilience.